Dampak Alokasi Dana Desa dan Program Pembangunan Desa Pada Kesejahteraan Mayarakat - Maro, Yustina (Peneliti.net, 2025)
Welfare is a condition where a person is safe, prosperous, and safe from various kinds of disturbances, problems difficulties, and so on. This study aims to determine the impact of village fund allocation and village development programs on the welfare of village communities in Mataru Selatan Village, Mataru District, Alor Regency with a population of village officials and the Mataru Selatan village community and a sample of 56 people. Data collection was carried out using a questionnaire while data analysis used a research instrument test, classical assumption test, and multiple linear regression using the t-test and F test. The results of the study showed that partially the allocation of village funds affected the Welfare of the Mataru Selatan Village Community, Mataru District, Alor Regency, as evidenced by a significance value of 0.000. Partially, the village development program affects the welfare of the people of Mataru Selatan Village, Mataru District, Alor Regency, as evidenced by a significance value of 0.000, and simultaneously, the allocation of village funds and the village development program affect the welfare of the village community in Mataru Selatan Village, Mataru District, Alor Regency, as evidenced by a significance value of 0.000.